Customer behavioral intentions for online purchases: An examination of fulfillment method and customer experience level - Boyer, Kenneth K.; Hult, G. Tomas M. (Journal of Operations Management, 2006)
AbstractThis study presents an analysis of the growing market for groceries and other foodstuffs ordered via the internet or telephone for delivery to the customer's home. This industry has been growing for the past 5 years at greater than 25% per year while the overall market for foodstuffs has been largely stagnant. The research utilizes data from surveys of over 2100 customers of five different home delivery grocers. The analysis utilizes two group variables (customer experience level and order picking method) and five primary constructs (service quality, product quality, product freshness, time‐savings and behavioral intentions). The results indicate that customer perceptions of the primary constructs generally improve as they gain experience with this new method of ordering and receiving groceries. Furthermore, the operational choice of picking method is also shown to have a large impact on customer perceptions—in particular, more experienced customers generally rate the primary constructs higher for distribution center (DC)‐based picking than for store‐based picking. The study provides support for the hypothesis that direct to customer foodstuffs can be of better freshness and quality when picked from a DC because of the ability to shorten the supply chain than from a store. The data suggest that a DC‐based picking strategy is viable if grocers can re‐shape customer perceptions and master the numerous intricacies of the supply chain.